PENAKSIRAN EFISIENSI BIAYA DAN LABA TERHADAP FAKTOR PERSAINGAN DI PERUSAHAAN ASURANSI UMUM INDONESIA - Awaloedin, Mulawarman; Sidik, Syahrial (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This study aims to assess the cost efficiency and profit of general insurance companies in Indonesia and analyze the influence of market competition factors on financial performance. The analysis methods used include logarithmic regression and the MANOVA test to test the simultaneous influence of independent variables on dependent variables. Market characteristics analysis is carried out to understand the market structure and distribution of companies based on asset categories and claims ratios. The results show that financial variables such as assets, leverage, and claims ratio have a significant influence on cost efficiency and profit. However, non-financial factors such as customer satisfaction, product innovation, and service quality have not been widely considered. Fierce market competition, as evidenced by the low value of the Herfindahl-Hirschman Index (IHH), has the potential to reduce profit efficiency as companies tend to lower premiums to attract customers. The influence of digitalization and the use of technology has not been analyzed in depth in this study, although it has great potential in improving cost efficiency and profits. The research gaps found include a lack of attention to non-financial factors, the impact of government regulations, market segmentation based on the type of insurance product, and the lack of international comparisons. Follow-up research can develop an analysis by considering non-financial factors, digital technology adoption, and regulatory influences more in-depth. Keywords: cost efficiency, profit, competitive factors, general insurers, logarithmic regression, MANOVA